Ionic assignment of Xe IV lines - Reyna Almandos, Jorge Guillermo (1985)
The Xe IV spectrum between 2280 and 6100 A emitted by a new model of a non conventional spectroscopic «ource, has been studied. Six hundred and sixty «even lines has been assigned to this ion by employing the conventional method of energy variation, and the characteristic form of the spectral lines resulting from this type of spectral lamp has been particularly considered.